UPAYA REHABILITASI DAN REKONSTRUKSI WILAYAH PASCA BENCANA ERUPSI GUNUNG MERAPI DI KECAMATAN KEMALANG KABUPATEN KLATEN PROVINSI JAWA TENGAH - Putri Cep Alam; Herbasuki Nurcahyanto; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Disaster management is a systematic and comprehensive effort to overcome all disasters quickly, precisely and accurately to reduce casualties and losses impacted. The study in the authors proposed is about rehabilitation and reconstruction in disaster management. Rehabilitation is ratification and recovery in all public service aspects or society to an adequate level in post-disaster areas by primary for normalization or walks fairly all government aspects and society in post-disaster areas.Reconstruction is rebuilding in all the infrastructures and facilities, the institutions in post-disaster areas, either at the government or society level by growth main target and economic activities, social, cultural, law enforcement development and the primary order, and also the rising of community participation all social life aspects in post-disaster areas.This study is motivated by the Merapi eruption in 2010 which resulted in many losses and damages in around Merapi area, losses and damages that required priority handling and robust reconstructing.This research is descriptive by using qualitative research methods, intended to analyze disaster management practice in the rehabilitation and reconstruction of infrastructural, economical, housing, and social sectors. The author conducted research in Kemalang, Klaten. Based on the author's research, the disaster management of rehabilitation and reconstruction needed priority treatment and disaster management knowledge to minimize damaging and losing after Merapi eruption. Rehabilitation and reconstruction activities required careful planning so that all victims will handle properly.